ANALISIS WACANA IKLAN POLITIK PEMILIHAN PRESIDEN DAN WAKIL PRESIDEN INDONESIA 2019 - Prihatin, Yulianah; Dawudi, Dandy Asghor (STKIP PGRI Jombang, 2019)
Globalization causes distance in the dimensions of space to be easily trimmed, this causes the dynamics of civilization to be increasingly aggresive in its movements, due to exchange and distribution of information is very easy, this reality also has an impact on the dynamics of politics in Indonesia. This research is a discourse analysis study that uses descriptive qualitative research methods. The object of this research process is discourse of political advertising contained in the 2019 Indonesian president an vice presidential election process. The formulation of the problem carried out in this study is what is contained as a marker of cohesion obtained in the discourse in the form of 2019 Indonesian presidential election political ads. The result of the analysis process show a data in the form Jokowi’s Political advertising discourse Ma’ruf is an anaphora and subtitution, and the result of the cohesion markings obtained on the objects of the political advertising discourse of Prabowo-Sandiaga are repitition and katafora. Furthermore, the marker of coherence obtained from the object of the political advertising discourse from Jokowi-Ma’ruf is the relation between consecutive and explanatory relationships, and the sign of coherence obtained from the object of the political adcertising discourse of Prabowo-Sandiaga is a parallel relationship. From the facts of reality that have been obtained from the research process found above, it can be concluded that the two objects of the discourse of political advertising are objects of good discourse.